2018
DOI: 10.1002/ange.201708889
|View full text |Cite
|
Sign up to set email alerts
|

Universality of the Sodium Ion Binding Mechanism in Class A G‐Protein‐Coupled Receptors

Abstract: The allosteric modulation of G‐protein‐coupled receptors (GPCRs) by sodium ions has received significant attention as crystal structures of several receptors show Na+ ions bound to the inactive conformations at the conserved Asp2.50. To date, structures from 24 families of GPCRs have been determined, though mechanistic insights into Na+ binding to the allosteric site are limited. We performed hundreds‐of‐microsecond long simulations of 18 GPCRs and elucidated their Na+ binding mechanism. In class A GPCRs, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
6
23
0
Order By: Relevance
“…Adaptive sampling has been shown to efficiently sample the large conformational changes in various important targets. [54][55][56][57][58][59][60] The adaptive sampling approach introduces sampling bias in the simulation dataset and this bias is eliminated during construction of Markov State Model (MSM). The sampling bias is introduced as simulations are started from the least populated states after each round.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Adaptive sampling has been shown to efficiently sample the large conformational changes in various important targets. [54][55][56][57][58][59][60] The adaptive sampling approach introduces sampling bias in the simulation dataset and this bias is eliminated during construction of Markov State Model (MSM). The sampling bias is introduced as simulations are started from the least populated states after each round.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Also, long timescale behavior of protein dynamics can be predicted using MSMs (Pande et al, 2010;Chodera and Noé , 2014;Shukla et al, 2015;Husic and Pande, 2018). MD simulations have been successfully employed to elucidate protein-ligand binding processes (Buch et al, 2011;Dror et al, 2011b;Plattner and Noé , 2015;Selvam et al, 2018b), understand conformational change processes in proteins (Nygaard et al, 2013;Yang and Roux, 2008;Moffett et al, 2017b), and identify key intermediate states of proteins (Shukla et al, 2014;Dror et al, 2011a). Moreover, our group recently utilized MD simulations to reveal an allosteric mechanism for inhibition of the plant receptor kinase BAK1 through PTM by S-glutathionylation (Moffett et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, computational studies turned their attention to the influence of sodium ion coordination in the A 2A AR affinity for antagonists, focusing less on the structural basis of the sodium-bound receptor’s inability to recognize agonists [14]. The sodium binding mechanism to 18 different GPCRs has been recently investigated through microsecond-scale molecular dynamics (MD) simulations [15]. Previous computational studies compared the allosteric binding site of the sodium ion in the A 2A AR inactive and active states, suggesting the latter conformation is characterized by an important reduction of the volume of the allosteric cavity, unfavorable to the ion coordination [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous computational studies compared the allosteric binding site of the sodium ion in the A 2A AR inactive and active states, suggesting the latter conformation is characterized by an important reduction of the volume of the allosteric cavity, unfavorable to the ion coordination [9,16]. Although it is now widely accepted that the recognition of the sodium ion at its allosteric binding site occurs from the extracellular side, it is more complex to computationally describe how the sodium may dissociate and how the agonist can play a role in this process [15]. Recent scientific work has shown that Na + can leave the allosteric site either by translocating in the cytoplasmic side or by retracing the binding path towards the extracellular environment.…”
Section: Introductionmentioning
confidence: 99%